DYNAMIC MODEL OF FLOOD AND TIDAL INUNDATION VULNERABILITY IN LOWLYING AREA, CASE STUDY AT SEMARANG - Suhelmi, IR; Fahrudin, A; Yulianda, F; Nuitja, INS (Badan Informasi Geospasial in Partnership with MAPIN, 2010)
Global warming will raise sea level, Intergovernmental Panel on Climate Change (IPCC) estimates that the water level rise globally from 1990 to 2100 will reach 23-96 cm. While the increase in world temperature over this time period of about 2oC to 4.5oC (IPCC, 1995). Due to an increase in sea water is a phenomenon of erosion and puddles in the coastal areas and loss of wetland that is rich in biodiversity. Semarang topography sloping to the slope tends to 0-2% with most of the area is almost the same height as the sea level and even in some places below him. In this way, the topography of the vulnerability to natural phenomena became increasingly large. This vulnerability becomes higher because of the phenomenon that the amount of land subsidence reach 15-25 cm per year. This paper will discuss various matters related to develop model of inundation caused by tidal inundation and the local flood. This paper will study various factors that affect the inundation of tidal flood that includes land subsidence, sea level rise and hight of tides. The study will use spatial data such as satellite imagery, Digital Elevation Model (DEM) and processed with Geographic Information Systems (GIS). Rainfall data, changes of landuse, run off and drainage capacity to help in building the models.Keywords: Dynamic Model, Inundation, Tidal Flood, Flood, DEMABSTRAKPemanasan global menyebabkan kenaikan permukaan laut, IPCC memprediksikan tingkat kenaikan air laut secara global rentang waktu 1990-2100 mencapai 23-96 cm. Peningkatan suhu dunia selama jangka waktu tersebut sekitar 2oC untuk 4.5oC (IPCC, 1995). Semarang, khususnya kota bawah, memiliki topografi yang datar antara 0-2% yang menjadikan kota ini sangat rentan terhadap fenomena kenaikan muka air laut. Kerentanan menjadi lebih tinggi dengan adanya fenomena amblesan tanah (land subsidence) yang mencapai 15 cm per tahun pada lokasi-lokasi tertentu. Tulisan ini akan membahas berbagai hal yang terkait model genangan yang disebabkan oleh banjir rob dan banjir lokal. Faktor yang mempengaruhi genangan rob meliputi penurunan tanah, kenaikan permukaan laut dan pasang surut air laut. Penelitian ini menggunakan data spasial seperti citra satelit, Digital Elevation Model (DEM) dan diproses dengan Sistem Informasi Geografis (GIS). Data curah hujan, perubahan tata guna lahan dan kapasitas drainase digunakan untuk membantu dalam membangun model.Kata Kunci: Model Dinamik, Kenaikan Permukaan Laut, Pasang Surt, Banjir, DEM